Distribution of Hepatitis B Virus Genotypes Among Patients at Internal Medicine Unit, Dr. Soetomo General Hospital, Surabaya - Citrawati Dyah Kencono Wungu; Mochamad Amin; Ulfa Kholili; Gwenny Ichsan Prabowo; Poernomo Boedi Setiawan; Soetjipto Soetjipto; Retno Handajani (Warmadewa University, 2019)
Background: Hepatitis B virus (HBV) infection is a major health problem worldwide, especially in developing countries. The study of HBV genotypes is important to find out the diversity of HBV genotypes related to the severity of the disease, response to therapy, and clinical symptoms. Objective: This study was aimed to detect HBV genotypes in patients at Hepatology Outpatient Clinic, Dr. Soetomo Hospital Surabaya. Methods: This study was conducted on new patients at Hepatology Outpatient Clinic of Dr. Soetomo General Hospital, Surabaya in one month. Nested PCR was performed by targetting HBV surface genes. Samples with positive HBV DNA were sequenced and analysed further. Results: In this study, a total of 27 samples were obtained. The prevalence of HBV infection shown by positive HBsAg in patients with symptoms of liver disease was 55.55% (15/27 patients). Based on the results of electrophoresis from PCR products, positive HBV DNA was obtained in these 15 patients (100%). After sequencing samples with positive HBV DNA, genotype B of Indonesian strain was found to be predominant genotype (100%). Subgenotype analysis showed that 7/15 samples had B3 subgenotype (46.67%). Conclusion: In patients at Hepatology Outpatient Clinic of Dr. Soetomo General Hospital, Surabaya, the prevalence of HBV infection was high (55.55%) and genotype B was predominant. In Surabaya, HBV genotype infection still remained like the previous pattern, although in Indonesia there have been many inter-island and ethnic migration. Further similar studies are needed to obtain the diversity of other HBV genotypes.